2020
DOI: 10.1177/2632077020965568
|View full text |Cite
|
Sign up to set email alerts
|

Person- and System-Focused Prevention in Preparing Youth to Navigate an Uncertain Work Future

Abstract: In this article, we discuss the integration of prevention science and vocational psychology for person- and system-focused prevention with a critical social justice agenda. More specifically, we focus on career development education as a potentially transformative primary prevention activity for increasing youth access to decent work and lives of well-being. We consider this as a critical agenda for two reasons. First, there are continued declines in the availability of decent work on a global level. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The models that were examined in this study are derived from those proposed by Duffy et al (2016). Research in vocational and developmental psychology suggests, however, that additional compensatory resources and individual assets may be relevant for high school and college students (Kenny & Tsai, 2020; Pan et al, 2018). Pan et al (2018), for example, found in a study of Chinese university students that internship quality moderated the relationship between proactive personality and career adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…The models that were examined in this study are derived from those proposed by Duffy et al (2016). Research in vocational and developmental psychology suggests, however, that additional compensatory resources and individual assets may be relevant for high school and college students (Kenny & Tsai, 2020; Pan et al, 2018). Pan et al (2018), for example, found in a study of Chinese university students that internship quality moderated the relationship between proactive personality and career adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research with youth and theoretical elaboration of decent education (Duffy et al, 2022) and the school-to-work transition (Masdonati et al, 2022) from a PWT perspective can inform an expanded view of career education, drawing from and extending the model of career education proposed by Kenny and colleagues (Kenny, Blustein, et al, 2019; Kenny & Tsai, 2020). Decent education affirms the role that education plays in cultivating the academic and vocational skills needed in the workplace and fostering psychological assets that are important for a successful school-to-work transition.…”
Section: Implications Of Pwt For An Expanded Vision Of Career Develop...mentioning
confidence: 99%
“…Recognition of the importance of decent work has led some organizations, such as the International Labor Organization (ILO), to claim that access to decent work is a fundamental human right (ILO, 2013). In recognition of the importance of decent work for well-being across adult life, some scholars (e.g., Kenny & Tsai, 2020) identify preparation for future work as a primary prevention and health promotion activity.…”
Section: Introductionmentioning
confidence: 99%
“…PWT has implications for both person-centered career development and systemic intervention (Blustein et al, 2019). At the person level, for example, intervention may seek to foster personal assets such as social support, critical consciousness, and proactive personality; while at the systems level, intervention focuses on implementing structural change that will reduce marginalization and economic constraints (Kenny & Tsai, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%